Recent advances on bifunctional catalysts for one-pot conversion of furfural to γ-valerolactone - Wang, Jianhua; Xiang, Zhiyan; Huang, Zexing; Xu, Qiong; Yin, Dulin (Frontiers in Chemistry, 2022)
γ-Valerolactone (GVL) is one of the most valuable compounds derived from Furfural (FAL), which has been industrially product from agricultural byproducts corncons. It is extremely challenging that synthesis of GVL from FAL efficiently via a one-pot cascade reaction due to the need for multiple active sites in a single pot. By focusing on the aspects of one-pot synthesis of GVL from FAL, the authors aim to shed light on the rational design and utilization of environmental-friendly bifunctional catalysts with high efficiency in this reaction. Perspectives regarding future research opportunities in bi- or multi-functional catalysts for one-pot GVL synthesis are also discussed.